Re-orienting the âWestâ? The Transnational Debate on the Status of the âWestâ in the Debates among Islamist Intellectuals and Students from the 1970s to the Present - Noor, Farish A. (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2009)
This paper will look at the process of transnational transfer of ideas, beliefs and value-systems, with a special emphasis on the transfer of Islamist ideas and ideals through the vector of student movements and organisations that were set up in Western Europe and North America as well as the rise of a new generation of Islamist intellectuals in Malaysia in the late 1960s for whom the idea of the âWestâ was turned on its head and re-cast in negative terms. It begins by looking at how the âWestâ was initially cast in positive terms as the ideal developmental model by the first generation of post-colonial elites in Malaysia, and how â as a result of the crisis of governance and the gradual decline in popularity of the ruling political coalition â the âWestâ was subsequently re-cast in negative terms by the Islamists of the 1960s and 1970s who sought instead to turn Malaysia into an Islamic society from below. As a consequence of this dialectical confrontation between the ruling statist elite and the nascent Islamist opposition in Malaysia, the idea of the âWestâ has remained as the central constitutive Other to Islam and Muslim identity, and this would suggest that the Islamist project of the1970s to the present remains locked in a mode of oppositional dialectics that nonetheless requires the presence of the âWestâ as its constitutive Other, be it in positive or negative terms.